Seerumin ja syljen tulehdusmerkkiaineiden yhteys akuuttien ylähengitystieinfektioiden esiintyvyyteen ja palautumiseen maratonin yhteydessä - Lehtonen, Oona (2025)
The aim of the study was to investigate the prevalence of upper respiratory symptoms and infections over a two-week period among marathon subjects and their matched controls. The study examined also pre-marathon risk factors that may increase the risk of infection. Among marathon runners, the relationship between serum (leukocytes, IL-1α, IL-1β, IL-4, IL-6, IL-10, IL-15, IL-23, IFN-γ, TNF-α) and saliva (COR, IgA) inflammatory markers and upper respiratory infections was investigated, as well as the impact of these markers on perceived physical and psychological recovery post-marathon. Upper respiratory tract infections (ARinf) are the most common health issue for athletes and in primary healthcare. High training loads and events like marathons can cause transient immune system disturbances, inflammation, and increase the risk of illness, particularly within 1–2 weeks after the event. Planning recovery is crucial for managing overall load and reducing illness risk.